EFEKTIVITAS HUKUM PERLINDUNGAN KONSUMEN DALAM E-COMMERCE: EVALUASI KRITIS DAN STRATEGI RESPONSIF - Uba Wohan , Ernesta; Ingraini Atitus , Maria Contasya; Dami , Laurensius Kaba; Teka , Ricardus Wesly; Seran , Yohanes Babtisto (Gapenas Publisher, 2025)
The advancement of digital technology has significantly transformed consumer behavior, particularly through electronic commerce (e-commerce) transactions. This phenomenon has raised various legal issues concerning consumer protection, such as fraud, inaccurate product information, and misuse of personal data. This study aims to (1) examine the legal foundations of consumer protection in e-commerce in Indonesia, (2) evaluate the effectiveness of its implementation, and (3) formulate more responsive and equitable legal strategies for digital consumers. This research employs a qualitative method with a literature study approach, focusing on statutory regulations and relevant academic journals. The findings indicate that Indonesia has a relatively comprehensive legal framework, including the Consumer Protection Law, the Electronic Information and Transactions Law, the Government Regulation on Electronic Commerce, and the Personal Data Protection Law. However, the implementation still faces several challenges, such as low compliance among business actors, weak supervision, and suboptimal dispute resolution mechanisms. Therefore, strategic legal measures are needed, including regulatory harmonization, enhancement of digital legal literacy, development of online dispute resolution systems (ODR), stricter law enforcement, and multi-stakeholder collaboration. This study is expected to contribute academically to the development of consumer protection in the digital economy era.